2018
DOI: 10.22271/ortho.2018.v4.i3j.94
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of age at menopause with bone mineral density in post-menopausal women: A prospective study

Abstract: Background: Osteoporosis is a major public health problem as it is associated with substantial morbidity and socioeconomic burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the study by Bi, there was a significant difference in serum COMP between patients with KL grades 2-4 with healthy control (KL 2: SMD = 0.86, 95% CI, 0.09, 1.62, P = 0.03; KL 3: SMD = 1.05, 95% CI, 0.01, 2.08, P = 0.05; KL 4: SMD = 0.99, 95% CI, 0.33, 1.65, P = 0.003). 13 A meta-analysis conducted by Bi (2018) reviewed 9 studies that provided knee KL OA degree data and had serum COMP level data in both OA and control patients. In the study conducted a subgroup evaluation to find out the relationship between serum COMP levels and the severity of OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Bi, there was a significant difference in serum COMP between patients with KL grades 2-4 with healthy control (KL 2: SMD = 0.86, 95% CI, 0.09, 1.62, P = 0.03; KL 3: SMD = 1.05, 95% CI, 0.01, 2.08, P = 0.05; KL 4: SMD = 0.99, 95% CI, 0.33, 1.65, P = 0.003). 13 A meta-analysis conducted by Bi (2018) reviewed 9 studies that provided knee KL OA degree data and had serum COMP level data in both OA and control patients. In the study conducted a subgroup evaluation to find out the relationship between serum COMP levels and the severity of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Bi based on his meta-analysis concluded that measurement of serum COMP levels can effectively distinguish OA from KL degrees ≥2. 13 Another study conducted by Kelman et al, examined COMP levels in female patients with post-menopause pelvic OA. COMP levels were found to be 13% higher compared to the group of patients who did not suffer from pelvic OA.…”
Section: Discussionmentioning
confidence: 99%